THE RELATIONSHIP BETWEEN SELF-ESTEEM AND SCHOOL CLIMATE WITH BULLYING BEHAVIOR AT SMPN 10 KEJURUAN MUDA - Shinta Oktora; Patisina; Hasanuddin (RADJA PUBLIKA, 2024)
This study aims to determine the Relationship between Self-Esteem and School Climate with Bullying Behavior at SMPN 10 Kejuruan Muda. This type of research is quantitative research with correlational methods.The population in this study was 150 students with the sampling technique being total sampling and the sample in this study was 120 students by conducting screening of students who behaved as bullies and the results of the trial.. The measuring instrument used is a Likert scale to measure Self-Esteem and School Climate with Bullying Behavior. The data analysis method used in this study is multiple regression analysis. The subjects in this study were students at Al Manar Medan with the results of the study showing that: (1) There is a significant negative relationship between self-esteem and bullying behavior as indicated by the coefficient = -0.525; p = 0.001 p <0.05, the results showed that self-esteem has a predictive power against bullying behavior of 27.5%. (2) There is a significant negative relationship between school climate and bullying behavior at Al Manar Medan as indicated by = -0.546; p = 0.000 p <0.05, the results showed that school climate has a predictive power against the emergence of bullying behavior of 29.8%. (3) There is a significant relationship between self-esteem and school climate with bullying behavior as indicated by the coefficient F = 12.039 R = -0.560 while = 0.313 with p = 0.000 P <0.05. Together, self-esteem and school climate have a predictive power towards the emergence of bullying behavior of 30.3%. From these results, it is known that there is still a 69.7% contribution from other factors or variables towards the formation of bullying behavior. From the results of this study, the proposed hypothesis is declared accepted.